ASSESSMENT OF INDICATORS OF ANXIETY AND DEPRESSION IN PATIENTS AFTER COVID-19 - Khanifa Mukhsinovna KHALIMOVA; Rustambek Jumanazarovich MATMURODOV; Xasan Rustam ugli TURAPOV; Bekzod Askarovich MUMINOV; Eldor Isroilovich ABDUKODIROV (Scholar Express Journals, 2023)
The indicators of anxiety and depression of patients after Covid-19, which is one of the medical and social problems. The degree of anxiety and depression was assessed using modern neuropsychological scales. Based on the obtained results, an algorithm for early diagnosis was developed.
Keywords: Covid-19; anxiety; depression